A Historical Review of Racial, Ethnic, and Gender Diversity in Plastic Surgery at the University of Michigan - Levy, Julien J.S.; Hooper, Rachel C. (Seminars in Plastic Surgery, 2024)
In this article, we examine the 60-year history of diversity efforts within the Section of Plastic Surgery at the University of Michigan (UofM) in the context of national trends. We describe the experiences of pioneering Underrepresented in Medicine (URiM) and female graduates of the program. James Norris, MD, and Christine Sullivan, MD, were the first URiM and female graduates from UofM in 1974 and 1989, respectively. Currently, women constitute over one-half the plastic surgery trainees at UofM, but URiM trainee representation remains limited. Dr. Adeyiza Momoh and Dr. Amy Alderman were the first URiM and female faculty members hired in 2011 and 2004, respectively. At present, there are four URiM and seven female faculty members in the Section. With a shared vision, supportive leadership, and motivation to change, faculty diversity has increased substantially. Additional strategies, including ongoing pipeline programs in medicine and science for URiM and women, are needed to further increase workforce diversity in plastic surgery.
Keywords: Underrepresented in Medicine (URiM); disparities; inequities; UofM